Unusual enantiomeric D,L-N-acyl homoserine lactones in Pectobacterium atrosepticum and Pseudomonas aeruginosa. - Umang Dhaubhadel; Abiud E Portillo; Ondřej Horáček; Yu-Sheng Sung; Daniel W Armstrong (PLoS ONE, 2023)
Quorum Sensing allows bacteria to sense their population density via diffusible N-acyl homoserine lactone (N-HL) signaling molecules. Upon reaching a high enough cell density, bacteria will collectively exhibit a phenotype. Until recently, methods used for detection of N-HLs have not considered the chirality of these molecules and it was assumed that only the L-enantiomer was produced by bacteria. The production and effects of D-N-HLs have rarely been studied. In this work, the temporal production of D-N-HLs by the plant pathogen Pectobacterium atrosepticum and the human pathogen Pseudomonas aeruginosa are reported. Both bacteria produced D-N-HLs in significant amounts and in some cases their concentrations were higher than other low abundance L-N-HLs. Previously unreported D-enantiomers of N-3-oxoacyl and N-3-hydroxyacyl homoserine lactones were detected in P. atrosepticum. Interestingly, L-N-HLs produced in the lowest concentrations had relatively higher amounts of their corresponding D-enantiomers. Potential sources of D-N-HLs and their significance are considered.